Community social capital and individual functioning in the post‐disaster context. Issue 2 (15th November 2018) - Zahnow, Renee; Wickes, Rebecca; Taylor, Mel; Corcoran, Jonathan
Abstract : Disasters can have severe and long‐lasting consequences for individuals and communities. While scholarly evidence indicates that access to social support can ameliorate their negative impacts, less understood is whether or not neighbourhood social capital can facilitate recovery. This study uses two waves of survey data—collected before and after a significant flood in Brisbane, Australia, in 2011—to examine the relationship between the severity of the event at the individual and neighbourhood level, access to neighbourhood social capital and individual‐level social support, and functioning in the post‐disaster environment. In line with previous research, the results indicate that the severity of the flood is the most salient predictor of post‐disaster functioning. No evidence was unearthed to show that neighbourhood social capital amassed before the flood leads to better functioning subsequently, but the findings do suggest that individual‐level social support can moderate the effect of flood severity on functioning.